Guidelines to improve waste management in portuguese construction industry - Couto, J. Pedro (2011)
The environmental impact of the construction activity has gained increasing importance in the last few years and has become a key challenge for the sector. The resulting inconveniences of the activities in a construction project are numerous. However, there are still many examples of an inefficient waste management. The deconstruction of buildings has gained more and more attraction in recent years as an important waste management tool. The aims of the present paper are discuss strategies and actions that should be implemented in Portugal to improve waste construction management by impelling the deconstruction process. It was clear the importance of National authorities and construction practitioners understand the benefits of the deconstruction process and look at it as an advantageous way to improve waste management, thus following other European countries’ practice.